ANALISIS PERTUMBUHAN EKONOMI JAWA TENGAH DAN FAKTOR YANG MEMPENGARUHI BERDASARKAN PDRB - Delfina; Jessica; Fionna Quinn; Jesseline Chang (Bajang Institute, 2022)
Economic conditions in Central Java Province have improved from time to time. So that a study was conducted to determine and analyze the factors that can affect the economic growth of Central Java Province for the 2020 period with reference to the 2015-2020 PDRB. The data is collected through the Central Java Statistics Agency and will be analyzed through the stages of data reduction, data display and conclusion drawing. The results of the analysis show that the increase in PDRB in 2015 to 2019 shows very good economic growth in Central Java but due to the pandemic period, PDRB in 2020 has decreased due to limited public consumption activities, government spending, investment and exports and imports. In the future, the Central Java Government can focus on infrastructure development and empowering the poor as well as creating open job opportunities for the unemployed.